A phase I/II study of adoptive immunotherapy using donor liver graft-derived NK cell-enriched immune cells to prevent severe infection after liver transplantation. - Masahiro Ohira; Yuki Imaoka; Koki Sato; Koki Imaoka; Tomoaki Bekki; Takuya Yano; Ryosuke Nakano; Hiroshi Sakai; Shintaro Kuroda; Hiroyuki Tahara; Kentaro Ide; Tsuyoshi Kobayashi; et al. (PLoS ONE)
Bloodstream infections (BSIs) are significant postoperative complications associated with high mortality rates after liver transplantation (LT). Natural killer (NK) cells, which are key components of the innate immune system, have demonstrated potential to combat both infections and cancer. The use of activated NK cells to mitigate post-LT infections, particularly BSIs, has attracted considerable interest. We conducted a single-arm Phase I/II clinical trial to evaluate the safety and efficacy of transfusing donor liver-derived NK cells into LT recipients. Patients were administered a single infusion of these NK cells three days post-LT. The primary endpoint was BSI incidence. This study was terminated in 19 patients because of the high incidence of BSIs. Of the 19 patients receiving immunotherapy, six (31.5%) developed BSIs within one month of LT. No adverse events were directly related to NK cell infusion. Acute rejection was noted in seven patients (36.8%). After infusion, NK cell activity in the recipient's peripheral blood remained stable. In conclusion, this clinical trial did not reach the primary endpoint. This could be attributed to a significant percentage of patients presenting with high immunological risk. Nonetheless, the infusion procedure demonstrated a favorable safety profile without serious adverse events.